Do Stock Investors Value Corporate Sustainability? Evidence from an Event Study - Wai Kong Cheung, Adrian (2011)
This paper analyzes the impacts of index inclusions and exclusions on corporate sustainable firms by studying a sample of US stocks that are added to or deleted from the Dow Jones Sustainability World Index over the period 2002–2008. The impacts are measured in terms of stock return, risk and liquidity. We cannot find any strong evidence that announcement per se has any significant impact on stock return and risk. However, on the day of change, index inclusion (exclusion) stocks experience a significant but temporary increase (decrease) in stock return. Liquidity deteriorates after the announcement day and bounces back significantly near the day of change. Systematic risk shows little change after announce- ments. But, idiosyncratic risk is higher after announcements. The overall results support Harris and Eitan’s (The Journal of Finance 41(4), 815–829, 1986) price pressure hypothesis, which posits that event announcement does not carry information and any shift in demand (and hence the corresponding price change and liquidity change) is temporary.
Keywords: characteristic-based benchmark model; Event Study; Dow Jones Sustainability World Index; Corporate Sustainability